Answer:
63+38=101
Step-by-step explanation:
Answer: o well i dont really knwo
Step-by-step explanation:
Answer:
The general equation following the pattern becomes is 7 + (n - 1)×2
Where, n = The figure number - 1
Step-by-step explanation:
The pattern in the question can be described as follows;
Figure 2 = (5 + 2) squares boxes = 7 squares boxes
Figure 3 = (5 + 2 + 2) squares boxes
Figure 4 = (5 + 2 + 2 + 2) squares boxes
Therefore, the number of squares boxes per figure, form an arithmetic progression (a + (n - 1)d) with the first term a = 7, the common difference d = 2, and the n = the nth term of the series, such that the general equation following the pattern becomes;
7 + (n - 1)×2.
Answer:
6 months, i used the equation from part a so i know it’s right
Step-by-step explanation:
a) 15 + 12x = 87
b) 12x = 87-15=72
72/12 = 6
On what do u Need help on?